Epidermolysis bullosa in a twins infant: a rare case - Sawitri; Rahmadewi; Medisika Hertanti, Dhea; Indrawati, Ditya; Zulkarnain, Iskandar; Citrashanty, Irmadita; Widia, Yuri (Bali Dermatology Venereology and Aesthetic Journal, 2023)
Background: Epidermolysis bullosa (EB) is a rare hereditary genodermatosis characterized by blisters due to trauma and temperature. Cases of EB in twin infants are rare. This report will discuss EB in twin infants to improve our knowledge about this genodermatosis. Case: A baby boy with a twins history aged 4 months was consulted by the Pediatric Department with complaints of fluid-filled blisters that have been present since birth. During examination, bullae appeared on the upper and lower extremities. The gram examination and culture results showed Staphylococcus aureus infection and gentamicin sensitivity. The histopathology results showed a subepidermal blister with the dermis layer showed lymphocytic infiltration, which was in accordance with EB. The baby was hospitalized for 5 days and then came back to the outpatient unit with his twin, who had the same complaint. Examination of the second infant revealed multiple erosions and hypopigmented macules on the superior and inferior extremities. Both babies were born at term, normal, adequate weight, and are the first twins. Direct immunofluorescence did not show immunoglobulin G (IgG) and complement C3 deposits in the basement membrane zone. Both infants received symptomatic therapy. Conclusion: Epidermolysis bullosa is a rare case, especially in twins. Electron microscopy is a gold standard for determining EB type. Symptomatic treatment is the main therapy in this population of EB.